Utemeljeni razlogi za izstop družbenika iz družbe z omejeno odgovornostjo - Podgorelec, Peter (Podjetje in delo, 2022)
Justified grounds for the withdrawal of a shareholder from a limited liability company are all those circumstances that make it unbearable for anyone to continue as a shareholder. They can be divided into the conduct of other shareholders, circumstances within the company's sphere, and personal circumstances of a shareholder who wishes to withdraw. The subsidiarity of the withdrawal must be considered. In relation to the circumstances within the company's sphere, it is disputed whether the occurrence of company's dependency constitutes justified grounds for the withdrawal. According to the author, the answer should be affirmative. A consensual withdrawal is also a possibility. Unless otherwise agreed, it is subject to the same legal consequences as the contractual and judicial withdrawal. If the articles of association stipulate conditions for the consent of shareholders, the nature of the shareholder's claim depends on the discretion left to the other shareholders for the decision.
Keywords: družba z omejeno odgovornostjo; izstop; justified grounds; legal personality; limited liability company; pravna osebnost; subsidiarity; subsidiarnost; utemeljeni razlogi; withdrawal